2013
DOI: 10.1016/j.mrgentox.2013.05.009
|View full text |Cite
|
Sign up to set email alerts
|

DNA synthesis inhibition in response to benzo[a]pyrene dihydrodiol epoxide is associated with attenuation of p34cdc2: Role of p53

Abstract: Our previous findings demonstrated that DNA damage by polynuclear aromatic hydrocarbons (PAHs) triggers a cellular protective response of growth inhibition (G1-S cell cycle arrest and inhibition of DNA synthesis) in human fibroblasts associated with accumulation of p53 protein, a growth-inhibitory transcription factor. Here, we report that BPDE (the ultimate carcinogenic metabolite of the PAH benzo[a]pyrene) treatment triggers a variable extent of inhibition of DNA synthesis/cell growth, which does not corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…NLRP1 expression is regulated by p53 ( 39 ). It is generally accepted that the p53 pathway can be activated by BaP exposure via genotoxic and non-genotoxic pathways, including ROS generation ( 41 , 42 ). We also observed that p53 phosphorylation was markedly enhanced by BaP treatment in A549 cells ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…NLRP1 expression is regulated by p53 ( 39 ). It is generally accepted that the p53 pathway can be activated by BaP exposure via genotoxic and non-genotoxic pathways, including ROS generation ( 41 , 42 ). We also observed that p53 phosphorylation was markedly enhanced by BaP treatment in A549 cells ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…[12] Thus, the inhibiting chemically induced carcinogenesis by Ab against PAHs is a potentially beneficial area of research 13 . On the other side recent studies have been carried out to assess the using Ab against PAHs for immune diagnostic of cancer.…”
mentioning
confidence: 99%